Some Legal Problems in Ensuring Human Security in the Conditions of Information and Psychological Warfare (Second Artsakh War Case) - Harutyunyan, Armen (Տիգրան Մեծ)
The quality of opposition and penetration possibilities are also altering in the rapidly changing world. In parallel with the technical and technological development, it seems that in pre-war, wartime and post-war proceedings, the informative and psychological components, if are not pushed to the forefront, do not concede to the military actions with their significance of influencing the opponent. The second war of Artsakh, which lasted from September 27 to November 9 in 2020 and the military crimes carried out by the Turk-Azerbaijani tandem during the war, shows that the policy towards Armeni-ans implemented by both Turks and Azerbaijani has not been changed over a century. That is, since 1918, all the tools with the military, informational, and psychological components used by Azerbaijan are initial-ly targeted not only at the azerbaijanization of the territories but also against the statehood of Artsakh and human rights. In this regard, it isimperative for the Armenian side to clearly and objectively convey the available in-formation of inhuman policy against Armenians to the international community.
Keywords: Social philosophy